A Caveat When Using Alkyl Halides as Tagging Agents to Detect/Quantify Reactive Sulfur Species - Xiaohua Wu; Yuping Xin; Qingda Wang; Yongzhen Xia; Luying Xun; Huaiwei Liu (MDPI AG, 2022)
Using alkyl halides to tag reactive sulfur species (RSSs) (H2S, per/polysulfide, and protein-SSH) is an extensively applied approach. The underlying supposition is that, as with thiols, RSS reacts with alkyl halides via a nucleophilic substitution reaction. We found that this supposition is facing a challenge. RSS also initiates a reductive dehalogenation reaction, which generates the reduced unloaded tag and oxidized RSS. Therefore, RSS content in bio-samples might be underestimated, and its species might not be precisely determined when using alkyl halide agents for its analysis. To calculate to the extent of this underestimation, further studies are still required.